Impact of soil characteristics on relative bioavailability of NDL-PCBs in piglets. (November 2015) - Delannoy, Matthieu; Fournier, Agnès; Tankari Dan-Badjo, Abdourahamane; Schwarz, Jessica; Lerch, Sylvain; Rychen, Guido; Feidt, Cyril
Highlights: Relative bioavailability of NDL-PCBs in soil was assessed in vivo. Piglet was used as a model of child to assess its exposure through soil ingestion. Focus on content and quality of organic matter was realized. Organic matter content is of major impact on relative bioavailability. Overall NDL-PCBs relative bioavailability is high for all tested soil (>45%). Abstract: Children may be orally exposed to organic pollutants through involuntary soil ingestion. This study was aimed at determining the impact of the characteristics (organic carbon (OC), black carbon (BC), clay contents and pH) of ten contaminated soils on the bioavailability of non-dioxin-like polychlorobiphenyls (NDL-PCBs). Five juvenile male piglets were exposed to increasing amounts of each of the soils. These soil-fed groups were compared by a relative bioavailability approach (RBA) to a reference group fed with corn oil spiked with increasing doses of Aroclor 1254. After 10 days of oral exposure, the animals were sacrificed and NDL-PCB concentrations were determined by GC–MS in the adipose tissue. The relative bioavailability (RBA) factors were calculated for PCB 101, 138, 153 and 180. Despite high variations in the amount of black carbon (0.50 g kg −1 –6.0 g kg −1  d.w.) and organic matter (12 g kg −1 –180 g kg −1  d.w.), only 3 soils exhibited a significantly lower RBA for all NDL-PCBs, compared to the oil-group. High levels of OC (>100 g kg −1 ) and BC content (3.0 g kg −1 ) were related to a significant reduction in RBA. Overall, RBA was higher than 45% independently of the soil and the PCB congener.